6 RELIGION, CONSCIENCE, AND MORALLY CONTROVERSIAL CLINICAL PRACTICES: RESULTS FROM A NATIONAL PHYSICIAN SURVEY. (1st March 2007) - Curlin, F. A.; Lawrence, R.; Chin, M. H.; Lantos, J. D.
Abstract : Background: There is heated public debate about whether health professionals may refuse to provide treatments to which they morally object. To date, there have been no studies of how physicians themselves think about their rights and obligations when such moral conflicts emerge in the clinical encounter. Methods: A cross-sectional, mailed survey of a stratified, random sample of 2, 000 practicing US physicians from all specialties. Primary criterion variables were physicians' judgments about their ethical rights and obligations when patients request a legal medical procedure to which the physician objects for religious or moral reasons. Results: Most physicians believe that, in such situations, it is ethically permissible for doctors to explain their moral objections to patients (63%). Most also think that physicians are obligated to disclose information about (86%) and refer the patient for (71%) requested procedures. Physicians who are male or religious or have personal objections to morally controversial clinical practices are less likely to believe that doctors must disclose information about or refer patients for morally contested medical procedures. Conclusions: In light of these findings, patients who want information about and access to legal but controversial medical interventions might inquire proactively to make sure that their physician would discuss or accommodate requests for these options. Such dialogue may be particularly important if the physician is male or religious or has known objections to other controversial treatments.